The Role of Educational Experiences in Shaping Work Adaptability in the Digital Era - Niki Novitasari (Pencerah, 2026)
The rapid transformation of the digital workplace has intensified the need for adaptability as a core competence. Despite its importance, existing studies tend to treat work adaptability as an outcome variable and often overlook the processes through which it develops. In particular, the relationship between educational experience and psychological resources in shaping adaptability remains underexplored. This study employs a qualitative phenomenological approach to explore how individuals experience the development of work adaptability. Data were collected through in-depth interviews with participants who had transitioned from formal education to the workforce. The data were analysed using thematic analysis to identify patterns related to educational experiences, psychological capital, and adaptive responses. The findings indicate that educational experiences involving exploration, ambiguity, and collaborative learning contribute to the development of psychological capital, including self-efficacy, resilience, optimism, and hope. These psychological resources function as internal mechanisms that enable individuals to navigate changing work demands. Work adaptability is understood as a dynamic and ongoing process shaped by the interaction between prior learning experiences and workplace contexts. This study demonstrates that work adaptability is not a fixed competence but a developmental process rooted in educational experience and mediated by psychological capital. The findings highlight the importance of designing educational practices that foster adaptive capacity alongside knowledge acquisition, offering both theoretical and practical implications for preparing individuals in the digital era.